The wet and the dry methods indigenous technological innovations in palm starch extraction in the Central Philippines - Paluga, Myfel Joseph D (Banwa, 2016)
At least up to the early twentieth century, sago processing practices from varied palm sources is widespread not just in Mindanao but throughout in the Philippines, among diverse ethnolinguistic groups from northern and southern Luzon, the Bicol region, Palawan and varied areas of the Visayas and Mindanao. The broad forms of palm starch extraction techniques can be grouped into the wet method (the usual approach throughout Southeast Asia and the Pacific, involving crucial steps which are not present in the former: slicing, drying, and using mortar-and pestle type of pounding). This highly important indigenous dry method was first reported as the "Argao dry process" of starch extraction by Dr. Dulce M. Flores. This chapter expands this direction originally hinted by Flores and presents historical evidence for its wider geographic distribution in the Philippines. As to its antiquity, the dry method points to Samar as the innovation's earliest recorded appearance (around 1660s). This technological innovation among ethnolinguistic groups, broadly called "Bisaya" in most colonial accounts but also encompassing the Bicol region (thus fitly mapping with what archaeologists and linguistics demarcate as Central Philippines), is most probably a unique Philippine innovation and shows a feature that differentiates the technological aspects of human-sago relations in the Philippines as compared to the rest of Southeast Asia and the Pacific.